1998
DOI: 10.1002/(sici)1521-3765(19980904)4:9<1852::aid-chem1852>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Si-H Activation in Titanocene and Zirconocene Complexes of Alkynylsilanes RC≡CSiMe2H (R=tBu, Ph, SiMe3, SiMe2H): A Model To Understand Catalytic Reactions of Hydrosilanes

Abstract: An agostic interaction between the Si–H bond and the metal center (depicted on the right) is the characteristic feature of the title complexes, which could be prepared by acetylene exchange reactions. IR, NMR, and X‐ray structural investigations reveal that the effect of the Si‐H‐metal interaction is considerably stronger at low temperatures and in the solid state. This mode of bond activation is important in active catalysts for hydrosilylation and dehydrogenative polysilane reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 54 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…20b Coordinated solvent can be replaced by η 2 -H-SiR 3 as illustrated previously in eq 64 as well as the displacement of coordinated THF by the "tethered" H-Si group in the HMe 2 SiCtCR complex of "Cp 2 Zr(THF)" to give 3-8. 139 A coordinated ClCH 2 Cl in [(OC) 3 L 2 M-(ClCH 2 Cl)] + (L ) P(OCH 2 ) 3 CMe] 2 ; M ) Mn, Re) and in [(OC) 4 L 2 Re(ClCH 2 Cl)] + was replaced by η 2 -H-SiEt 3 in the formation of 3-57, 3-62, and 3-63. 168,171 In the remaining examples in this section, addition of hydrosilane resulted in an increase in the electron count of an electronically and coordinatively unsaturated metal complex.…”
Section: Addition Of Silanes To Metals and To Low-valent Metal Complexesmentioning
confidence: 99%
See 4 more Smart Citations
“…20b Coordinated solvent can be replaced by η 2 -H-SiR 3 as illustrated previously in eq 64 as well as the displacement of coordinated THF by the "tethered" H-Si group in the HMe 2 SiCtCR complex of "Cp 2 Zr(THF)" to give 3-8. 139 A coordinated ClCH 2 Cl in [(OC) 3 L 2 M-(ClCH 2 Cl)] + (L ) P(OCH 2 ) 3 CMe] 2 ; M ) Mn, Re) and in [(OC) 4 L 2 Re(ClCH 2 Cl)] + was replaced by η 2 -H-SiEt 3 in the formation of 3-57, 3-62, and 3-63. 168,171 In the remaining examples in this section, addition of hydrosilane resulted in an increase in the electron count of an electronically and coordinatively unsaturated metal complex.…”
Section: Addition Of Silanes To Metals and To Low-valent Metal Complexesmentioning
confidence: 99%
“…139 The M · · · H · · · Si interaction depicted by the authors resembled the composite structure shown in Scheme 15B as well as A in Figure 9 (for R ) SiMe 2 H). In the titanium case, it could be shown that bulky Cp ligands (Cp* and THI) provided sufficient steric hindrance to prevent the formation of the -agostic interaction.…”
Section: -Agostic Interactionsmentioning
confidence: 99%
See 3 more Smart Citations